Empirical Model on Teachers Perception of Students Employability Skills on Arts and Science Colleges in Tamil Nadu - Dr. M. Sakthivel Murugan, Dr. S. Ganapathy (International Journal of Modern Agriculture, 2020)
The basic education provides the foundation for learning secondary, teritary education and India needs a flexible education system. The basic thing is to provide the foundation for learning; secondary and tertiary education to develop core capabilities and core technical skills; and further means of achieving lifelong learning. The education system should be accustomed to the new global environment by promoting creativity and improving the quality of education and training at all levels”. The flexibility in the education system can be described in the preface of the World Bank document talks about the rigid determination of the educational institutions in adapting to the global environment. Skill, the ability, competence, dexterity, knack, aptitude, proficiency, expertise, and cleverness which manifests itself in various ways is used for the various purposes. Green F (2011) explains that “the skill levels have large economic effects for individuals, employers, regions and whole national economies. He argues that there is no consensus among social scientists, economists, sociologists and psychologists, in each one philosophy which sounds different as if it appears to be talking about different things”. Employability skills are need of the hour for students, faculties and educational institutions. In this context, this paper id aimed at developing an empirical model of employability skills of the college students as per the opinion of their teachers who are working in colleges the teachers are brain behind the students in curriculam development as well as designing and developing employability skills of students for their employment.